2013
DOI: 10.18740/s4j016
|View full text |Cite
|
Sign up to set email alerts
|

The Pacification of the American Working Class: A Time Series Analysis

Abstract: In this paper we operationalize and empirically test six core tenets of pacification theory derived from Marxian political economy using time series data for the USA from 1972-2009. Our analysis confirms that rising inequality is statistically significantly correlated to increased public and private policing over time and that increased public and private policing is also statistically significantly correlated to increased industrial exploitation as measured through "surplus-value". While unionization correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…While state policing formations and notions of police science were well entrenched in continental Europe, these public forms were eventually met with competition from private policing agencies (Button, 2007; Johnston, 1992; Rigakos, 2000; Shearing and Stenning, 1983). Today, it is a well understood empirical reality that the private sector outnumbers the public police sector in almost all capitalist economies (de Waard, 1999; Jones and Newburn, 1995; Rigakos and Ergul, 2013; van Steden and Sarre, 2007). It is thus no surprise that the size of the private security sector has typically vacillated alongside developments in securing wage labour, extracting surplus value and enforcing class relations as evidenced through the strong correlation between economic inequality and total policing, both public and private, per population (Rigakos and Ergul, 2017).…”
Section: Private Security Work Under Turkish Neoliberalismmentioning
confidence: 99%
“…While state policing formations and notions of police science were well entrenched in continental Europe, these public forms were eventually met with competition from private policing agencies (Button, 2007; Johnston, 1992; Rigakos, 2000; Shearing and Stenning, 1983). Today, it is a well understood empirical reality that the private sector outnumbers the public police sector in almost all capitalist economies (de Waard, 1999; Jones and Newburn, 1995; Rigakos and Ergul, 2013; van Steden and Sarre, 2007). It is thus no surprise that the size of the private security sector has typically vacillated alongside developments in securing wage labour, extracting surplus value and enforcing class relations as evidenced through the strong correlation between economic inequality and total policing, both public and private, per population (Rigakos and Ergul, 2017).…”
Section: Private Security Work Under Turkish Neoliberalismmentioning
confidence: 99%
“…It is here that the concept of pacification becomes useful as a critical tool for understanding police power. Recent work (Neocleous, 2010(Neocleous, , 2011(Neocleous, , 2013Neocleous and Rigakos, 2011;Rigakos and Ergul, 2013) has suggested that rather than being a concept restricted to imperial conquests conducted in bygone times, pacification can be usefully reclaimed as a tool for critical theory 'for analysing the broad vision of police and capital' (Rigakos, 2011: 78) in the contemporary context. The history of pacification demonstrates that it is a productive process, never solely involved in simply suppressing resistance in both imperial and domestic settings, but instead consciously employed in the construction of a new social order.…”
Section: Policing As Pacificationmentioning
confidence: 99%
“…Neocleous links Marx's idea around the violence of accumulation as a fundamental process of pacification. Rigakos and Ergul (2013) further connect pacification to police powers through a Marxist lens by saying,…”
Section: The Revival Of Pacification: a Different Interpretationmentioning
confidence: 99%
“…And the police are a central component to this process. Rigakos and Ergul (2013) explain that "[p]acification is the continuum of police violence upon which the fabrication of capitalist order is planned, enforced and resisted" (p. 169). Neocleous (2011) insists that the historical origins of pacification and its first instance of usage are significant for connecting Marx's idea about bourgeois and security.…”
Section: The Revival Of Pacification: a Different Interpretationmentioning
confidence: 99%
See 1 more Smart Citation